Conversational Implicature Analysis in “Kingdom of Heaven” Movie Script by William Monahan - Saiful Akmal; Desy Ulfa Yana (Buletin Al-Turas, 2020)
This study was designed to discover the types of conversational implicature and the non-observance maxim of cooperative principles expressed by the characters in the Kingdom of Heaven movie script by William Monahan. The theory of Grice was applied to analyze the conversational implicature, and the qualitative approach is used to explain the conversational implicatures. After analyzing the movie, we discovered particularized implicatures as the most frequent conversational implicatures in the movie script with 14 occurrences, followed by six occurrences of generalized implicatures. The finding also revealed that the frequent use of flouting maxim of quantity occurred more frequent with 14 out of the total 20 excerpts, with violating maxim found only three times in the movie script. From this study, both findings suggested the reason behind the frequent use of flouting maxim compare to violating maxim in conversational implicature is because the speaker assumes that they will be in a safe position, and then expect the hearer to understand their points, as the speaker did not intentionally manipulate or mislead the hearer.